ClaG: A classification system for plays and games in toy libraries and libraries - Carlo Bianchini; Paolo Munini (JLIS.it, 2025)
The paper presents ClaG, a novel classification system for plays and games created for the Archivio Italiano del Gioco (AIG) [Italian Games Archive], Udine, Italy. The primary goal of the classification system is to serve as a practical tool for highlighting the characteristics of a game that are useful for the selection, research, identification, and delivery of a game, or a set of games, to a player or group of players using a game library or a library with a game collection. This objective guided all the decisions in its construction. The identification of the main relevant concepts was based on a twofold approach: a top-down strategy, by the identification of general concepts from specialized literature on play and game, and a bottom-up strategy, involving the recursive application and modification of these concepts to classify a set of 200 games (mainly table and board games). The paper elucidates the five fundamental concepts that underpin the construction of this classification: space, materials, setting, game outcome, and genre and provides a comprehensive overview of the classification system. To evaluate the classification system's effectiveness, it was presented twice to a panel of experts who appreciated it and offered suggestions for improvement. The results indicate that the resulting classes are very small, each containing only a few items. Finally, the paper discusses prospects for the future development and use of the classification system.